Development of millimetre-wave heterodyne array for airborne and space satellite mission - Tan, B; Wenninger, J; Yassin, G (IEEE, 2022)
In this paper, we present our latest works on developing the various generic technologies to find the innovative solutions for constructing a heterodyne focal plane array, based on the Superconductor-Insulator-Superconductor (SIS) mixer technology. This includes the use of the planar superconducting circuit technology to replace the commonly used bulky waveguides or optical components, therefore simplifying the radio frequency (RF) operation and minimising the size of the array. We will describe the design of a novel easy-to-machine feed horn technology which enables deployment of large arrays with minimal cost. This technology has been demonstrated successfully and has since been deployed in various existing and up-coming telescopes. We then demonstrate these capabilities by presenting the design and built of a small pixel-count array near 220 GHz range, combining both the E- and H-polarisation chains within a single mixer block. Finally, we briefly describe our recent works on the superconducting parametric amplifier technology that could potentially replace the conventional semiconductor amplifiers that are power hungry and dissipate large amount of heat, which render the construction of large arrays difficult.